Investigation of the secondary porosity in ill-crystallized or desilicated ZSM-5 zeolites and its performance on MTH reaction - Silva, Laura L. [UNESP]; Florindo, Bianca R. [UNESP]; Catuzo, Gabriel L. [UNESP]; Zapelini, Iago W.; Cardoso, João Victor S.; Luna, F. Murilo T．; Cavalcante, Célio L.; Martins, Leandro [UNESP] (Elsevier, 2022)
The use of zeolites in several fields, especially in base or acid-catalyzed reactions and adsorption, depends on their physical and chemical properties tuned by modification of the synthesis (bottom-up methods) or post-synthesis procedures (top-down). Among the various possibilities, three stand out: (1) the embryonic zeolites, (2) partially formed or ill-crystallized structures, and (3) the desilication of consolidated zeolites by consuming part of the zeolitic structure in an alkaline solution. The modifications of zeolites aim to obtain materials with secondary porosity, mainly for improved applications as catalysts in reactions that form deactivating coke, as usually seen in the conversion of methanol to hydrocarbons (MTH). Herein, amorphous, partially crystallized, and fully-grown ZSM-5 zeolites were prepared and later characterized to establish the synthesis-property function in MTH. Finally, the completely crystallized ZSM-5 zeolite was desilicated, and acid leached to create different structural and morphological properties. These modifications aimed to evaluate the various porosities and correlate them with the accessibility to catalytic sites and their effect on catalyst deactivation. The Zero-Length Column (ZLC) method was used to evaluate the diffusional behavior of methanol in all fresh synthesized samples. After the MTH, external and internal coke within the spent catalyst samples were extracted and analyzed by GC-MS. The size distribution of occluded carbonaceous molecules was associated with the porosity of the catalysts. Besides the typical polyaromatic compounds, oxygen-containing cycloalkenes were also formed inside the zeolitic pores. On the other hand, bulky linear oxygenates and paraffin were predominant on the outer surface. The hierarchical zeolites were more resilient to deactivation by coke, even after 28 h of reaction, keeping selectivity to light and heavy hydrocarbons longer than the purely microporous catalysts. As a result, a more outstanding production of aromatic compounds is directly related to increased material pore volume.
Keywords: Benzene-toluene-xylenes; Hierarchical zeolites; Methanol-to-hydrocarbons; Olefins; Partially crystallized zeolites